Equity in the Age of the Internet: Google Inc. v. Equustek Solutions Inc. - Berryman, Jeff (2019)
The Supreme Court of Canada’s decision in Google Inc. v Equustek has been criticized as amounting to an excessive claim of extra-territorial reach and possibly a way to bring the right to be forgotten to Canadian shores. In this comment, the author argues that the case is in fact an orthodox application of equitable principles, and one that stresses the importance of the notion that equity acts in personam. On occasion, equity does purport to exert an influence on a litigant’s conduct which takes place beyond the court’s geographical jurisdiction, but it does so, mindful of the practical limitations on enforcement of such orders.
Keywords: Jeff Berryman